A high emissivity coating with a sacrificial interface layer on ceramic fiber fabric for high temperature application. Issue 10 (15th May 2022) - Han, Pengda; Zhao, Jiansen; Jiao, Mengyu; Li, Jiangtao; Guo, Linlin; Yang, Shuo; Hu, Xiaoxia; Du, Haiyan
Abstract: The reaction or tight bonding between thermal insulation coating and the base ceramic fiber cloth is the main reason of the cloth embrittlement and failure. In this paper, the sacrificial interface layer is applied on aluminosilicate fiber cloth to inhibit the reaction between SiC-MoSi2 -SiB6 high emissive coating and the cloth. The sacrificial interface layer will be pyrolyzed at high temperature. The obtained space effectively prevents the glass formed by oxidation or melting of high emissive coating from contacting or reaction with the fibers in the cloth. The influence of different thickness of the middle layer and external coating on the micro morphology and mechanical properties of the fiber cloth was comprehensively compared and studied. The reusable performance of the coating was evaluated. The tensile strength of the fiber cloth with the optimized interface layer and external coating is about 40 MPa after heat treatment at 1300 °C for 1 h, which is 71.2% higher than that of the bare cloth; the tensile strength of the sample with only the outer coating and no intermediate layer is only 10 MPa after heat treatment at 1200 °C for 1 h. The bonding strength of the coating will not be obviously reduced by the application of sacrificial interface layer. By means of the interface layer the thermal shock resistance of the coating is improved. After 10 thermal shock cycles, the coating with a suitable interface layer is not cracking and spalling, and the bonding strength of it is as high as 125 kPa, the tensile strength is still as high as 20 MPa.